2015
DOI: 10.4149/gpb_2014040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacology of antihistamines in inhibition of oxidative burst of professional phagocytes

Abstract: Antihistamines of the H 1 and H 3 /H 4 groups interfere with oxidative burst of human professional phagocytes in vitro. In the concentration of 10 μM, H 1 antihistamines of the 1 st and 2 nd generation inhibited oxidative burst of human neutrophils in the rank order of potency: dithiaden > loratadine > brompheniramine > chlorpheniramine > pheniramine. Of the H 1 antihistamines, the most effective was dithiaden in suppressing oxidative burst of whole human blood and dosedependently the chemiluminescence of isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…This was confirmed in isolated neutrophils by measuring the intracellular chemiluminescence (Drábikova et al 2009) decreasing it in the rank order of potency curcumin > resveratrol > N-feruloylserotonin > quercetin. The intracellular inhibition of luminol-enhanced CL with antioxidants is dose-dependent and differs for the substances investigated (Nosáľ et al 2015, Jančinová et al 2012a. On the other hand, all the compounds tested decreased extracellular isoluminol-enhanced CL corresponding to their scavenging activities for oxidants, most probably as a result of the physico-chemical structure of their molecules, as demonstrated for H1 antihistamines (Králová et al 2009).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This was confirmed in isolated neutrophils by measuring the intracellular chemiluminescence (Drábikova et al 2009) decreasing it in the rank order of potency curcumin > resveratrol > N-feruloylserotonin > quercetin. The intracellular inhibition of luminol-enhanced CL with antioxidants is dose-dependent and differs for the substances investigated (Nosáľ et al 2015, Jančinová et al 2012a. On the other hand, all the compounds tested decreased extracellular isoluminol-enhanced CL corresponding to their scavenging activities for oxidants, most probably as a result of the physico-chemical structure of their molecules, as demonstrated for H1 antihistamines (Králová et al 2009).…”
Section: Discussionmentioning
confidence: 87%
“…The results showed that the compounds tested inhibited oxidative burst in stimulated whole human blood as measured by luminol-enhanced chemiluminescence (CL). The inhibition of stimulated chemiluminescence was found to be dose dependent for H1 antihistamines (Nosáľ et al 2015), carvedilol (Nosáľ et al 2005) and many polyphenolic compounds (Jančinová et al 2012a). Since the generation of reactive oxygen species was induced with PMA bypassing membrane receptors and stimulated protein kinase C, the inhibitory effect with three therapeutically used drugs (bromphenyramine, carvedilol and dithiaden) and five polyphenols (arbutin, curcumin, N-feruloylserotonin, quercetin and resveratrol) appeared intracellularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are represented by the H1-antihistamines (Drábiková et al, 2006 a,b; Jančinová et al, 2006 a , b ; Nosáľ et al, 2005) and carvedilol (Nosáľ et al, 2009 ). The pyridol derivative stobadine (Drábiková et al, 2007 ) and a number of natural compounds like glucomannans (Drábiková et al, 2009 ), arbutin (Jančinová et al, 2007 ), curcumin (Jančinová et al, 2009 ) and N-feruoyl serotonin (Nosáľ et al, 2015 ) demonstrated antioxidant activity on stimulated neutrophils in vitro . Many pharmacologically active drugs, like glucomannans, significantly decreased oxidative burst of blood phagocytes in the model of rat adjuvant polyarthritis (Drábiková et al, 2009 ; Jančinová et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Professional phagocytic cells play a central role in defending the host against microorganisms by producing reactive oxygen species (ROS) via the NADPH oxidase enzyme complex (Raad et al, 2009 ). A number of therapeutically used drugs and natural compounds with antioxidative properties have been demonstrated to interfere with oxidative burst of human whole blood and isolated neutrophils (Nosáľ et al, 2015 , 2014 , 2011 , Jančinová et al, 2015 , 2009 ), When appropriately stimulated by a variety of stimuli, they undergo dramatic physiological and biochemical changes. These are resulting in phagocytosis, chemotaxis and degranulation with the activation of ROS production in a metabolic pathway known as respiratory burst (O’Dowd et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%